ХАЛЫҚ ПЕДАГОГИКАСЫНДА ЖАСЛАРҒА АСТРОНОМИЯЛЫҚ БИЛИМ БЕРИЎ МАЗМУНЫ ҲӘМ ОНЫҢ ТУРМЫСЛЫҚ ӘҲМИЙЕТИ - Алеуов, Ө.; Бекимбетова, А. (FAN va JAMIYAT, 2016)
The article is devoted to the study of the youth‘s astronomical knowledge in folk Pedagogy. The life on the earth and people‘s life are connected with the movement of the sun, the moon and stars.